Pengaruh Kelengkapan Produk, Lokasi Pelayanan Dan Tata Letak Terhadap Keputusan Pembelian Pada Toko Jaya Raya Cabang Pemaron Singaraja - I Gusti Made Oka Astana; Ni Putu Wendy Katrina (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
. In Sharp Competition like this, usually the success of many companies is determined by the accuracy of the company in taking advantage of opportunities and identifying activities in an effort to obtain and use goods or service. One is building shop sells a variety of building materials. The purpose of this study was to determine the effect of product completeness, location, service and layout on purchasing decisions at the Jaya Raya Store branch pemaron singaraja. This research uses a quantitative approach. Data collection techniques used in this study were in the from of questionnaires, with measuring instruments in the form of agree-disagree scale, in which selected respondents were consumers at the Jaya Raya Shop branch pemaron singaraja ad many as 95 people. All the relationship variables examined in this study showed significant results related to the existence of the completeness of the product, location service, and layout of the purchasing decisions at the jaya raya shop branch pemaron. For that reason, in its realization, the jaya raya shop branch of the pemaron expected to be able to improve the completeness of the product, location,service, and layout so that it can improve purchasing decisions at the jaya raya shop of the branch pemaron.